Andy Warhol - Ratcliff, Carter; Abbeville Press (New York : Abbeville Press, 1983)
Presents a brief biography of Andy Warhol and discusses his works and their influence on the art world
Pre-pop -- Pop -- Post-pop -- Artist's statements -- Notes on technique -- Chronology -- Exhibitions -- Public collections
Includes bibliographical references (pages 123-126) and index
Keywords: Warhol, Andy, -- 1928-1987